Pengaruh Penerapan Permainan Edukatif Teka-Teki Silang dalam Pembelajaran Pendidikan Agama Kristen Terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 1 Satu Atap Tampahan Kabupaten Toba Tahun Pembelajaran 2024/2025 - Mita Analisa Sipayung; Rida Gultom; Oloria Malau; Tiurma Barasa; Pestaria Pestaria (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
The study aims to determine whether the educational crossword puzzle game can create, build, and change students' learning motivation and the learning process in class VIII of SMP Negeri 1 Satu Atap Tampahan. The research method used is quantitative with a pre-experimental design type in the form of One group pretest-posttest. The population of all classes VIII is 90 people and a sample of 31 people using purposive sampling. The closed questionnaire instrument consists of 20 items. The results of the data analysis show that there is an influence of the educational game method used by the teacher on students' learning motivation, as evidenced by the significant test obtained a value of t count> t table, namely 6.669> 2.042, it is concluded that H0 is rejected and Ha is accepted.